Primary Metabolism in Avocado Fruit - Pedreschi, Romina; Uarrota, Virgilio; Fuentealba, Claudia; Alvaro, Juan E.; Olmedo, Patricio; Defilippi, Bruno G.; Meneses, Claudio; Campos-Vargas, Reinaldo (Frontiers in Plant Science, 2019)
Avocado (Persea americana Mill) is rich in a variety of essential nutrients and phytochemicals, thus consumption has drastically increased in the last ten years. Avocado unlike other fruit is characterized by oil accumulation during growth and development and presents a unique carbohydrate pattern. There are few previous and current studies related to primary metabolism. The fruit is also quite unique since it contains large amounts of C7 sugars (mannoheptulose and perseitol) acting as transportable and storage sugars and as potential regulators of fruit ripening. These C7 sugars play a central role during fruit growth and development, but still confirmation is needed regarding the biosynthetic routes and the physiological function during growth and development of avocado fruit. Relatively recent transcriptome studies on avocado mesocarp during development and ripening have revealed that most of the oil is synthesized during early stages of development and that oil synthesis is halted when the fruit is harvested (pre-climacteric stage). Most of the oil is accumulated in the form of triacylglycerol (TAG) representing 60 to 70% in dry basis of the mesocarp tissue. During early stages of fruit development, high expression of transcripts related to fatty acid and TAG biosynthesis have been reported and downregulation of same genes in more advanced stages but without cessation of the process until harvest. The increased expression of fatty acid key genes and regulators such as PaWRI1, PaACP4-2 and PapPK-β-1 have also been reported to be consistent with the total fatty acid increase and fatty acid composition during avocado fruit development. During postharvest, there is minimal change in the fatty acid composition of the fruit. Almost inexistent information regarding the role of organic acid and amino acid metabolism during growth, development and ripening of avocado is available. Cell wall metabolism understanding in avocado, even though crucial in terms of fruit quality, still presents severe gaps regarding the interactions between cell wall remodeling, fruit development and postharvest modifications.